2013
DOI: 10.1111/opn.12028
|View full text |Cite
|
Sign up to set email alerts
|

‘Balancing risk’ after fall‐induced hip fracture: the older person's need for information

Abstract: The concept of balancing risk aims to help healthcare professionals understand the older person's perspective of hip fracture and to recognise the efforts that people make to guard against further injury and dependence in the early postdischarge period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(73 citation statements)
references
References 30 publications
0
73
0
Order By: Relevance
“…The patient need for information from health-care professionals and the importance of this in successful rehabilitation has also been previously identified. 298 A qualitative study of physiotherapist perceptions of rehabilitation also found that there is tailoring of care to patients' individual needs, based on their own goals and level of support available. 185 A study into the challenges of team working in the rehabilitation of hip fracture patients also demonstrated that there are breakdowns in communication within multidisciplinary teams and issues relating to the organisation of resources and services that lead to variation in patient care.…”
Section: Comparison With Previous Literaturementioning
confidence: 99%
“…The patient need for information from health-care professionals and the importance of this in successful rehabilitation has also been previously identified. 298 A qualitative study of physiotherapist perceptions of rehabilitation also found that there is tailoring of care to patients' individual needs, based on their own goals and level of support available. 185 A study into the challenges of team working in the rehabilitation of hip fracture patients also demonstrated that there are breakdowns in communication within multidisciplinary teams and issues relating to the organisation of resources and services that lead to variation in patient care.…”
Section: Comparison With Previous Literaturementioning
confidence: 99%
“…Six studies had been conducted in Sweden, three in the UK, two in Canada; the remaining five in Denmark, Norway, New Zealand, Australia or the USA. The studies covered data gathered at admission [23, 24], two weeks [25], one month [26], two to four months [27][28][29][30] or six to 12 months after discharge from hospital [31][32][33]. One study had a time frame from three months to 22 years after fracture [34]; the remaining four studies gave no indication of the time of interviewing [35][36][37][38].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The patients were thus wary of performing common daily activities, such as using a low armchair, worrying that they might not be able to rise from it, or cleaning, doing the laundry, shopping, going for a walk outdoors, driving a car or using public transportation [26, 28,38]. Overall, the unreliability of their body and their sense of fragility left them feeling vulnerable [23,26,27,29,30,37].…”
Section: ) Physical Healthmentioning
confidence: 99%
See 2 more Smart Citations